2021
DOI: 10.1001/jamaneurol.2021.3895
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Risk of Parkinson Disease Following Influenza and Other Infections

Abstract: Influenza has been associated with the risk of developing Parkinson disease, but the association is controversial. OBJECTIVE To examine whether prior influenza and other infections are associated with Parkinson disease more than 10 years after infection. DESIGN, SETTING, AND PARTICIPANTS This case-control study used data from 1977 to 2016 from the Danish National Patient Registry. All individuals with Parkinson disease, excluding those with drug-induced parkinsonism, were included and matched to 5 population c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 55 publications
1
53
3
Order By: Relevance
“…In a population-based casecontrol study in Canada, a significant association was reported to exist between a history of severe influenza and PD [88]. Recently, a case-control study based on the data of over 60 000 individuals from the Danish National Patient Registry showed that a history of influenza was significantly associated with a later occurrence of PD [89]. In addition, the Spanish flu (influenza A subtype H1N1) has been considered to be a risk factor for a later PD occurrence.…”
Section: Viral Infections Pd and H 2 S Producing Gut Bacteriamentioning
confidence: 99%
“…In a population-based casecontrol study in Canada, a significant association was reported to exist between a history of severe influenza and PD [88]. Recently, a case-control study based on the data of over 60 000 individuals from the Danish National Patient Registry showed that a history of influenza was significantly associated with a later occurrence of PD [89]. In addition, the Spanish flu (influenza A subtype H1N1) has been considered to be a risk factor for a later PD occurrence.…”
Section: Viral Infections Pd and H 2 S Producing Gut Bacteriamentioning
confidence: 99%
“…The role of H1N1 as a susceptibility agent has been recently validated in a retrospective study examining risk for developing Parkinson’s disease in humans following influenza 40 . This study showed that previous influenza infection resulted in the risk for developing Parkinson’s disease increased by 173% compared to individuals not infected 40 . This increase susceptibility was within the confidence interval determined epidemiologically for people born during the time of the 1918 H1N1 pandemic 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, using a similar approach to this study, we previously showed that mice that recovered from an influenza (strain ca/09 H1N1) infection developed enhanced susceptibility to the parkinsonian toxin MPTP 39 . The role of H1N1 as a susceptibility agent has been recently validated in a retrospective study examining risk for developing Parkinson’s disease in humans following influenza 40 . This study showed that previous influenza infection resulted in the risk for developing Parkinson’s disease increased by 173% compared to individuals not infected 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we presented two approaches to demonstrate the importance of reporting complete procedures of identifying patients from the DNPR. In practice, other approaches can be used, for example, researchers might identify patients who had a primary or a secondary diagnosis of a disease of interest, 13 patients who had a primary diagnosis of disease of interest leaving alone other kinds of information. 14 , 15 Which approach should be used depends on type of disease and purpose of research and needs to be explored further, which was, however, beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%